(untitled) (Research, Society and Development, 2023)
Introduction: Intracranial hypertension (IH) is a clinical condition secondary to the loss of cerebral compensatory mechanisms. There are distinct methodologies used to diagnose IH and among them is the brain4care (b4c) sensor, which allows non-invasive monitoring of intracranial volume and pressure variations, intracranial compliance. Objective: To characterize the epidemiological profile of patients with suspected IH in the pediatric age range. Method: A cross-sectional study was carried out in a reference pediatric hospital in Brazil, with patients with signs and symptoms of IH monitored with the non-invasive B4C sensor. The patients underwent neurological evaluation and were submitted to exams - ophthalmological evaluation, lumbar puncture, magnetic resonance imaging (MRI) and computed tomography (CT). Result: 58 patients were evaluated, of whom 32 are female (55.2%) and 26 are male (44.8%); most patients presented symptoms such as drowsiness (81%), nausea (77.6%), headache (74.1%), vomiting (63.8%). The ophthalmoscopic examination 77.6% (n=58) of the patients did not show signs of papilledema. On CT and MRI, no changes were found in 84.5% (n=58) and 69.2% (n=26), respectively. Lumbar puncture showed changes in 57.1% (n=21). Considering the interpretation that would be made in adult patients, the b4c sensor monitoring (n=58) showed probable changes in the lying and sitting positions, respectively, in 46.3% and 38.9%. Conclusion: It was found that the b4c device can provide a possible complement of clinical information in the process of monitoring cerebral compliance.